Formal and informal volunteering and health across European countries - Damiano Fiorillo; Nunzia Nappo (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
In this paper, we compare the correlation among formal and informal volunteering and self-perceived health across 13 European countries after controlling for socio-economic characteristics, housing features, neighborhood quality, size of municipality, social and cultural participation and regional dummies. We find that formal volunteering has a significantly positive association with self-perceived health in Finland and the Netherlands, significant negative relationship in Belgium, but none in the other countries. By contrast, informal volunteering has a significantly positive correlation with self-perceived health in France, the Netherlands, Spain, Greece and Portugal, and a significantly negative relationship in Italy. Our results point out that although formal and informal volunteering are correlated one with another they represents different aspects of volunteering whose correlations with self-perceived health depend, among others, on social and cultural characteristics of each country.
Keywords: I10; D64; P5; Z1; 330; self-perceived health; formal and informal volunteering; European countries